DESIGNING USER INTERFACE AND USER EXPERIENCE ON LAND MAPPING SYSTEM USING HUMAN CENTERED DESIGN APPROACH - Ilmi, Ahmad Rizal; Budianto, Alexius Endy; Harianto, Wahyudi (Jurnal Fakultas Teknologi Informasi, 2024)
Tanggung Village with all the diversity of its people requires that the need for agricultural land is still limited because the process of delivering information to the community in Tanggung Village regarding land mapping and distribution of subsidized fertilizers is still not optimal. In this case, researchers designed the Land Mapping System application with a User Interface that is easily understood by community users, to get feature specifications that are in accordance with the needs, the SIPETA Application must have a good User Interface (UI) and User Experience (UX) so as not to cause new problems and differences in interpretation in its use. Using mixed methods, this research applies Human Centered Design as the basis for designing an application design named SIPETA (Sistem Pemetaan Tanah). This research will focus on two main issues, namely related to the process of designing the SIPETA user interface and analyzing users of the Land Mapping Information System (SIPETA) in providing agricultural information to farmers in Tanggung Village. The result of this research is a concrete application that can be applied to the land data collection process and makes it easier for the village officials to manage it.